(untitled) (Journal of Asian Development Studies, 2014)
The purpose of this paper is to demonstrate the impact of Islamic work ethic (IWE) on employee work performance (EWP) and organizational commitment (OC) playing mediation role in the relationship of IWE and EWP. The valid and reliable scales were used for measuring the IWE, OC and EWP. 150 questionnaires were distributed among the employees of different public sectors’ organizations and 107 employees responded among them. The results (R square = 0.11) founded that there was significantly positive relationship between Islamic work ethics on employee work performance and when organizational commitment enter as mediator in their relationships the result (R square = 0.25) was also positively significant on employee work performance and this results (R square change 0.14) shown that organizational commitment was played complete mediation role, hence all the hypothesizes of this study were significantly confirmed at p value (p < 0.001). While the study was limited to the Pakistani public sectors’ organizations and sample size is too short, it has considerable implications for the development of a bright workforce in the other cultures and multinational organizations. An interpreting of the commitment of the manpower to the IWE and helps HR managers in designing the intervention, and implementation of this intervention to bring changes in public sector organizations for development of the employees and organizational effectiveness. In the results there is very strong necessary for the public sectors’ organizations in Pakistan as well as other non-western countries that examine the link of IWE and employee work performance by increasing the commitment level of employees. This paper emphasizes on IWE to improve the employee work performance by increasing the commitment level of employees in public sector organizations.